Inflation Targeting with NAIRU Uncertainty and Endogenous Policy Credibility - Isard, Peter; Eliasson, Ann-Charlotte.; Laxton, Douglas (Washington, D.C. : International Monetary Fund, 2001)
Stochastic simulations are employed to compare performance of monetary policy rules in linear and nonlinear variants of a small macro model with NAIRU uncertainity under different assumptions about the way inflation expectations are formed. Cases in which policy credibility is ignored or treated as exogenous are distinguished from cases in which credibility and inflation expectations respond endogenuously policy credibility strengthens the case for forward-looking inflation forecast based rules relative to backward-looking Taylor rules.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet